Modernization of public space floor and its impact on area - the example of the Kościuszko Square in Białystok = Modernizacja podłogi przestrzeni publicznej i jej wpływ na funkcjonowanie obszaru na przykładzie Rynku Kościuszki w Białymstoku - Tofiluk, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The last 25 years have been in many Polish cities a period of intensive modernization and renewals of the existing public spaces. Most of all the resurfacing of the pavement and changing of street furniture have been held. In many cases, the transformations in the urban areas were integrated with exclusion from traffic. The question arises what criteria architects or landscape architects follow and what design solutions apply.
Keywords: przestrzeń publiczna; nawierzchnia; podłoga miasta; mała architektura; public space; street furniture; pavement; urban floor